Thyroid lipomatosis in a patient of post renal transplantation - Kalluri, Meena R.; Balusu, Kavya; Marda, Sachin; Gowda, Sreehari (International Surgery Journal, 2022)
Thyroid lipomatosis is a rare benign disease with very few cases available in literature. We report a case of a 48 year old Indian male who presented with progressive swelling in front of neck since 5 years and difficulty breathing in lying down position along with difficulty in swallowing for the last 2 months. He is a known case of post renal transplantation for chronic kidney disease due to secondary AA amyloidosis. Total thyroidectomy was done and histopathology showed diffuse thyroid lipomatosis, with no evidence of amyloid deposition or papillary carcinoma. Fatty tissue is not commonly detected within the thyroid gland. Here we have reviewed the literature and discussed various differential diagnosis of thyroid lipomatosis.